Repercussions of absolute and time-rated BMI “yo-yo” fluctuations on cardiovascular stress-related morbidities within the vascular-metabolic CUN cohort - Sánchez-Iñigo, Laura; Navarro-González, D.; Martinez-Urbistondo, D.; Pastrana, J. C.; Fernandez-Montero, A.; Martinez, J. A. (Frontiers in Endocrinology, 2023)
Aims: The association between body mass index (BMI) fluctuation and the BMI fluctuation rate with cardiovascular stress morbidities in a Caucasian European cohort was evaluated to ascertain the impact of weight cycling. Methods: A total of 4312 patients of the Vascular-Metabolic CUN cohort (VMCUN cohort) were examined and followed up during 9.35 years (±4.39). Cox proportional hazard ratio analyses were performed to assess the risk of developing cardiovascular stress related diseases (CVD) across quartiles of BMI fluctuation, measured as the Average Successive Variability (ASV) (ASV=|BMIt0-BMIt1| + |BMIt1-BMIt2|+ |BMIt2-BMIt3|+…+|BMItn-1-BMItn|/n-1), and quartiles of BMI fluctuation rate (ASV/year). Results: There were 436 incident cases of CVD associated events involving 40323.32 person-years of follow-up. A progressively increased risk of CVD in subjects with greater ASV levels was found. Also, a higher level of ASV/year was significantly associated with an increased risk of developing CVD stress independent of confounding factors with a value of 3.71 (95% CI: 2.71-5.07) for those in the highest quartile, and 1.82 (95% CI: 1.33-2.50) for those in the third quartile. Conclusions: The BMI fluctuation rate seems to be a better predictor than BMI fluctuation of the potential development of cardiovascular stress morbidities. The time-rated weight fluctuations are apparently more determinant in increasing the risk of a CVD than the weight fluctuation itself, which is remarkable in subjects under “yo-yo” weight patterns for precision medicine.